Management of CRPS Type-I: Combination of stellate ganglion block and continuous brachial plexus block (ultrasound-guided): Case report - Dwarkadas Kanhayalal Baheti; Vaibhavi Baxi; Shweta Chandankhede (Indian Journal of Pain, 2014)
The complex regional pain syndrome (CRPS) I is a neurogenic pain syndrome that is characterized by pain, vasomotor and dystrophic changes and often motor impairments. The etiology of the condition resides in multiple theories, and diagnosis can be difficult and therapy focuses on pain management and restoration of physical function. The conservative treatment includes both non-pharmacological and pharmacological methods, and invasive therapy is centered on sympathetic and somatic blocks. We report a case of CRPS type-I in a 15-year-old young boy following repeated trauma to right elbow, which was successfully managed by a stellate ganglion block and continuous interscalene brachial plexus block and function restored to its full extent.